Penguatan Pendidikan Karakter Pada Masyarakt Kenalip Kelurahan Pamenang Kecamatan Pamenang Kabupaten Merangin - FITHRI AZNI (Jurnal Ilmiah Wahana Pendidikan, 2023)
The implementation of family education does not only act as a routine and natural implementer, but also acts as a manager who is responsible for laying the foundation, giving weight and direction for the pattern of children's lives. character is the psychological, moral, and character traits that distinguish one person from another; morals and character so that the generation is able to have quality mentally/morally, morally, and with character. In the study, the following results were obtained: 1) The strategy applied in instilling religious character education in children aged 7-12 years by applying a strategy of giving examples about the application of religious values, habituation of the behavior of children's daily religious values, enrolling children in madrasa institutions and involve children in religious activities in daily life. 2) The form of strengthening carried out by parents in instilling religious character education in children aged 7-12 years through providing advice, mentoring and giving moral sanctions in the form of neglecting children. 3) Obstacles faced by parents in instilling religious character education in children aged 7-12 years in the Kenalip community, Pamenang Village, Pamenang District, Merangin Regency, are laziness, the influence of TV shows, use of cellphones and peers/children's games. Therefore, in the future, parents will provide more examples in carrying out religious activities and emphasize that religion is the main foundation in life as religious people and is consistent in providing reinforcement to children.